Doped cap layer effect on impurity-free vacancy enhanced disordering in InGaAs/InP quantum well structures - An, Yu-Peng; Wang, Yi-Ding; Cao, Feng (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Strong influence on impurity-free vacancy enhanced disordering by the cap layer doping is studied on the InGaAs/InP quantum well structure with a doped cap layer. The observations are consistent with intermixing experiments using both Si3N4 and SiO2 as encapsulation dielectric layers. The largest intermixing occurs in the n-InP capped samples and is explained by the enhancement in out-diffusion of positive ions by the built-in electric field.
Optica Applicata, Vol. 40, 2010, nr 1, s. 249-254
Keywords: optyka; point defects; interdiffusion; built-in electric field